From England to Bohemia: Heresy and Communication in the Later Middle Ages. By Michael van Dussen - Tanner, Norman (The journal of theological studies, 2013)
It is paradoxical that the period of the Great Schism from 1378 to 1417, when western Christendom was torn apart by loyalties between two and later three popes, should coincide with a period of exceptionally close religious links between England and Bohemia. These close links between the two countries are the principal focus of the present study. The originality of the work lies in its being the first book-length study of the cultural and religious exchanges between the two countries during this period, as well as the result of many archives in Czechoslovakia becoming accessible after the end of the Cold War and the effective independence of the country in 1989 (pp. 1 and 5).